Exploring the recombinant evolution and hosts of crucivirus based on novel oyster-associated viruses - Zhang, Hong-Sai; Liu, Chang; Liu, Guang-Feng; Chen, Yu-Yu; Zhu, Peng; Xu, Xin; Yin, Bing-Xin; Jiang, Jing-Zhe (Frontiers in Microbiology, 2025)
“Crucivirus” represents a group of viruses with chimeric genomes, significant for viral evolution and recombination studies. Their capsid proteins share homology with the RNA virus tombusvirus, while their replicase-associated proteins are homologous to a class of single-stranded DNA viruses, namely CRESS DNA viruses. This study identifies seven novel crucivirus genomes from oysters cultivated along the coast of the South China Sea. Phylogenetic analysis reveals that five sequences form a distinct branch, which may indicate the presence of a new subclass within the crucivirus family. We analyzed crucivirus from multiple perspectives, including viral genomes, hallmark proteins, sequence similarity, and potential hosts. The results indicate that the crucivirus genomes and replicase-associated proteins (Rep) from oysters conform to the typical characteristics of crucivirus; Crucivirus Rep appears to have a direct parallel origin from multiple clades of CRESS DNA viruses, while only the S-domain of their capsid proteins shows some evolutionary relationship with tombusvirus. We found protein sequences in rotifers that are highly similar to the Cap three-dimensional structure of crucivirus, which may suggest host relevance. Overall, this study provides new insights into the classification, evolution, and host origins of crucivirus.